Synthesis of fluorescent stilbene and tolan rotaxanes by Suzuki coupling - Stanier, C; O'Connell, M; Clegg, W; Anderson, H (2001)
Highly fluorescent stilbene and tolan cyclodextrin [2]rotaxanes have been synthesised in good yield using aqueous Suzuki coupling, and the crystal structure of one of these rotaxanes has been determined.